Verticillium dahliae transcription factors Som1 and Vta3 control microsclerotia formation and sequential steps of plant root penetration and colonisation to induce disease - Tri‐Thuc Bui; Rebekka Harting; Susanna A. Braus‐Stromeyer; Van‐Tuan Tran; Miriam Leonard; Annalena M. Höfer; Anja Abelmann; Fruzsina Bakti; Oliver Valerius; Rabea Schlüter; Claire E. Stanley; Alinne Batista Ambrósio; et al. (2018)
Verticillium dahliae nuclear transcription factors Som1 and Vta3 can rescue adhesion in a FLO8-deficient Saccharomyces cerevisiae strain. Som1 and Vta3 induce the expression of the yeast FLO1 and FLO11 genes encoding adhesins. Som1 and Vta3 are sequentially required for root penetration and colonisation of the plant host by V. dahliae. The SOM1 and VTA3 genes were deleted and their functions in fungus-induced plant pathogenesis were studied using genetic, cell biology, proteomic and plant pathogenicity experiments. Som1 supports fungal adhesion and root penetration and is required earlier than Vta3 in the colonisation of plant root surfaces and tomato plant infection. Som1 controls septa positioning and the size of vacuoles, and subsequently hyphal development including aerial hyphae formation and normal hyphal branching. Som1 and Vta3 control conidiation, microsclerotia formation, and antagonise in oxidative stress responses. The molecular function of Som1 is conserved between the plant pathogen V. dahliae and the opportunistic human pathogen Aspergillus fumigatus. Som1 controls genes for initial steps of plant root penetration, adhesion, oxidative stress response and VTA3 expression to allow subsequent root colonisation. Both Som1 and Vta3 regulate developmental genetic networks required for conidiation, microsclerotia formation and pathogenicity of V. dahliae.